(untitled) (Journal of Tropical Pharmacy and Chemistry, 2015)
This research aims to determine the identification of secondary metabolites and antibacterial activity of ethyl acetate fraction of Jengkol fruit peel (Pithecellobium jiringa (Jack) Prain.) against the bacteria Pseudomonas aeruginosa and Bacillus subtilis. Identification of secondary metabolites is done by testing be qualitative. Antibacterial activity assays performed by agar diffusion method with a test concentration are 0,5%, 1%, 5%, 10% and 15%. The results of identification of secondary metabolites are flavanoid, fenolic and tannin. Data has been analyzed with measuring the diameter of the kill zone of ethyl acetat fraction of Jengkol fruit peel against bacterial growth. The result of research showed that ethyl acetat fraction of Jengkol fruit peel produce radical zone. The effective concentration of ethyl acetate of Jengkol fruit peel was 15% against the bacteria Pseudomonas aeruginosa and Bacillus subtilis.